The Effect of Advertising Tax Extensification and Intensification on Regional Tax Revenue - Melin Archanggela; Shinta Goddess Herawati (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
This study aims to find out about the effect of the extensification and intensification of advertisement tax on Bandung regional tax revenues. The object of research in this study is advertising tax extensification, advertising tax intensification, and local tax revenue. The research method used in writing this research is the case study method. This research was conducted at the Management Agency Regional Income of Bandung City. The population in this study is the number of advertisement taxpayers, advertisement tax receipts, and regional tax receipts for the period 2010 - 2018. Statistical tests using multiple linear regression analysis were processed using IBM SPSS Statistics, with a significant level of 5%. The results of this study indicate that advertisement tax extensification partially has no effect on regional tax revenue and advertisement tax intensification influences regional tax revenue, and the advertisement tax extensification and intensification simultaneously influence the effect on regional tax revenue.